Cover Feature: Mechanistic Insights into Fe Catalyzed α‐C−H Oxidations of Tertiary Amines (ChemCatChem 1/2021). Issue 1 (7th December 2020) - Legacy, Christopher J.; Hope, Taylor O.; Gagné, Yohann; Greenaway, Frederick T.; Frenette, Mathieu; Emmert, Marion H.
Abstract : The Cover Feature shows cast iron catalysis: Trialkyl amines cooked with the right recipe will take the oxygen from water to form the corresponding trialkyl amide. This transformation is iron‐catalyzed with a peroxyester acting as the oxidizing agent, picolinate as a ligand and pyridine as the solvent. In their Full Paper, C. J. Legacy et al. present mechanistic studies including initial rate kinetics, Eyring studies, kinetic isotope effects, a Hammett plot, reaction kinetic profile, oxidant probe study, EPR characterization of the iron site and DFT studies. Taken together, the data suggests a rate limiting step where an intramolecular α‐C−H abstraction occurs on the amine bound to an Fe(IV)‐oxo species. Tasty! More information can be found in the Full Paper by C. J. Legacy et al.